Efeitos do ciclamato de sódio na placenta de ratas: estudo morfométrico. - Matos, Marcelo Alexandre de (2006)
Objective: To evaluate the effects of sodium cyclamate on the rat placenta by its administration in the period of embryogenesis. Method: The sodium cyclamate was administered by intraperitoneal route in rats of the treated group at the dose of 60 mg/kg, from the tenth to fourteenth day of gestation, while the equivalent volume of saline solution was given to the control group, by the same route. On the twentieth day of pregnancy, 10 fetuses (5 from each group) were chosen at random for study. The technique of cariometry was utilized for evaluation of nuclear parameters of cells in deciduous and spongy layers, and of chorionic villi in the rat placenta. Results: The weights of treated fetuses and their placentas were less than those of the control group, while umbilical-cord length in the treated group was shorter than that in control fetuses. There were no alterations in the deciduous layer. In the placental spongy layer were found alterations of the following parameters: major diameter, mean diameter, perimeter, area, volume, the volume/area ratio and eccentricity. The altered parameters in chorionic villi were the following: mean diameter, perimeter, area, volume, the volume/area ratio. Conclusions: This study demonstrated placental alteration with the use of cyclamate by the pregnancy rat, and its repercussion in fetal weight and umbilical-cord length.